CELL TRANSMISSION MODEL (CTM) METHOD FOR SIMULATING VARIOUS TRAFFIC FLOWPROBLEMS INCLUDING TRAFFIC NETWORK - Faustin Indira P, Ignes
Traffic congestion problems commonly occur in major cities in Indonesia, and sometimes traffic adjustment is needed. Traffic engineers need a traffic simulator to make appropriate traffic adjustment decisions. This thesis will focus on the study of the Cell Transmission Model (CTM) method, a numerical approach that is commonly used in traffic simulators to make accurate traffic management decisions. First, it is shown that the CTM method is a discrete implementation of the kinematic model by Lighthill, Whitham, and Richards (LWR) with traffic flux (vehicle flow) in the form of a trapezoidal or triangular function. Next, the form of shock waves and rarefaction waves on a homogeneous road segment is simulated, and the result is consistent with the analytical solution formulated by Daganzo (1992). Furthermore, the CTM scheme is developed to accommodate traffic diverges (when there are road branches) and traffic merges (when two road segments merge). In the end, the CTM scheme is applied to simulate the dynamics of traffic flow in a traffic network case, with various turning movement parameters. Turning movement is a parameter that indicates driver preference in choosing certain routes. Simulation results show that the CTM method can display different traffic density values, depending on the chosen turning movement parameters. Such simulations can be used by traffic engineers in making decisions related to traffic adjustment.